Providing Medical Care to Patients with Abdominal Injuries at the Prehospital Stage in Moscow - D. N. Grekov; A. A. Ageeva; G. A. Vvedenskiy; E. V. Chernyakov; Z. A. Bagateliya; R. Yu. Maer; V. A. Kadyshev (Здоровье мегаполиса)
Introduction. The prevalence of injuries seems to be a modern challenge. For many decades, injuries have been the main cause of unnatural death and disability among the working population. These trends are especially pronounced in big cities. Nowadays, injuries are characterized by multiple and combined natureы, as well as high severity.Purpose. To analyze the features of abdominal injuries, to identify the correlation between the time of medical evacuation from the accident scene to a specialized hospital department and the outcomes in order to improve the treatment results.Methods and materials. Upon the data obtained from Moscow Emergency Medical Care Station, a selective retrospective analysis of 5,692 cases of abdominal injuries in Moscow for the period from January 1, 2020, to January 1, 2023 was carried out. To process and display the results, a statistical analysis using graphical methods (bar charts, histograms, range charts), the Kruskal-Wallis rank test and chi-square test was performed.Results. Among the total number of victims with severe injuries, abdominal trauma occurs in 20% of cases. The overall mortality rate of victims with abdominal injuries with isolated injury ranges 8–10%, reaching 60% in combined injury cases. The structure of the organization and the strategy for providing medical care to trauma victims in Moscow are aimed at implementing measures for timely hospitalization of patients and reducing mortality rates.